Pengaruh Penerapan Sistem Informasi Manajemen Perencanaan, Penganggaran, Dan Pelaporan (SIMRAL) Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Jeneponto - Milka Pasulu; Hasliah Hasliah; Pragemini Pragemini (AkMen JURNAL ILMIAH, 2022)
The study aimed to determine the effect of the implementation og the Budgeting and Reporting Planning Management Information System on of the quality of the Financial report of the Jeneponto Regency Goverment. Methode research that is used is quantitative methode using simple linear regression. The result of this study are various variables that effect othervariables. Based on SPSS output shows a positiveand significant influence on the information system of budgeting planning and reporting (SIMRAL) on the quality of fiinacial reporters on Jeneponto Government This is Indicated by the cofficient test or t test that is obtained by the value of t count of 4.592 this value is greater than T table which is 3.10 or t count 4.592 > T table 3.10 and frustraters with probability (sig) = 0.000 k 0,005. Because nialial prospourityis much smaller than 0,05 maka Ho is rejected and ha is published . This it can be cocluded thatb SIMRAL Variabel (X) has a positive and significant effect on the quality of variabel (Y) financial statetments in The Jenepomto Regency Government